Low salt stress affects physiological parameters and sugarcane plant growth - Cruz, Flávio José Rodrigues [UNESP]; Júnior, Domingos da Costa Ferreira [UNESP]; dos Santos, Durvalina Maria Mathias [UNESP] (Southern Cross Publishing, 2018)
Sugarcane is a renewable source for biofuel production and widely grown in tropical regions of the world. However, its cultivation might be limited in regions with soils affected by high level of soluble salts. This work was carried out aiming to evaluate the response of the sugarcane cultivar IAC91-1099 to low soil salinity under pot conditions, based on the hypothesis that low salt stress affects sugarcane growth. The experimental design was completely randomized, formed by the control treatment and 800 mg Na kg-1 soil. After twenty-five days of transplanting, the plants were submitted to the treatments and after thirty days under saline stress, the plants were harvested and the variables evaluated. Plants under salt stress presented higher Na content and Na/K ratio, and lower K content. Water status of sugarcane plants was impaired due to salt stress, expressed by lower values of stomatal conductance, relative water content and water potential. Na accumulation induced a decline on plant growth and higher electrolyte leakage, with damage to the photochemical apparatus of photosynthesis. Although sugarcane is considered a moderately salt tolerant crop, cultivar IAC91-1099 was sensitive to the low salt stress studied, not being recommended for cultivation in regions with pronounced soluble salt soil contents.
Keywords: Chlorophyll fluorescence; Growth; Osmotic stress; Relative water content; Salinity